Motivation Regulation among Black Women Triathletes - Candace S. Brown (MDPI AG, 2019)
There is a paucity of information on motivation among U.S. minority triathletes. This study aimed to understand the extrinsic motivation and regulators of Black women triathletes using a modified version of the valid Motivations of Marathoners Scale and semi-structured interviews, for triathletes. The Self Determination Theory guided the dual method assessment of the extrinsic motivators and the regulators external, introjection, and integrated. Using MANOVA, data from (N = 121) triathletes were compared across participant categories of age, body mass index, and distance. Results showed a significant age difference with younger women displaying more motivation. Descriptive means indicated integration as the greatest regulator of motivation. The statements ‘to compete with myself’ and ‘to be more fit,’ had the highest means among the women. A sub-sample of 12 interviews were conducted revealing 16 extrinsic themes. Six were related to the regulator integration and two unexpectantly related to the regulator, identified. Integrated themes, including coping mechanisms, finishing course, improvement, accomplishment, and physical awareness were most represented. This research fills gaps of understanding extrinsic motivation and the regulators of a group not previously explored. Future research on motivation among triathletes may benefit knowing how motivations are regulated, as to promote personalized training and participation.